A comparative study of learning patterns of secondary school, high school and college students. (March 2021) - Song, Yu; Vermunt, Jan D.
Highlights: Compare learning patterns used by secondary school, high school and college students. Learning patterns are similar between school students but different from college ones. They all show strong relationships with parents' education level and parents' jobs. Help to develop better support for students in adapting to new study environments. Abstract: The main aim of the current research was to identify the similarities and differences in learning patterns used by secondary school, high school and college students. There were 8, 072 participants and they responded to the Chinese version of Inventory of Learning Styles (ILS) online. Findings show that the three groups of students were significantly different in their adoption of learning patterns; the dimensionalities of learning patterns observed in secondary school and high school students were similar, but were different from those of college students; these students' learning patterns differed from each other in relation to personal characteristics (i.e. gender and age), but tended to have similar strong relationships with parents' education level and parents' jobs. This study contributes to the understanding of the learning patterns characterized by school and college students. By acknowledging this, educators can help to develop better support for students in adapting to new study environments.